Kto założył miasto Częstochowę? Przyczynek do urbanizacji Małopolski w XIV wieku - Nabiałek, Karol (Średniowiecze Polskie i Powszechne, 2019)
The article is an attempt to verify the circumstances concerning the founding of the town of Częstochowa, in particular the person of the initiator of the location. Historiographers have argued about the identity of the town’s founder for years, with some favoring Duke Vladi‑ slaus II of Opole and others King Casimir III the Great. In the most recent monograph of Częstochowa (2002), the assumption has been made that the founder of the city was indeed the Duke of Opole, even though there are not many grounds to make such claim. The main prem‑ ise seems to be the oldest mention of the city, dating back to the rule of Vladislaus II (1377). However, there exists significantly more proof that points to a pre-planned and executed over time expansion strategy initiated by Casimir III, which was preceded by the location of villages and crowned with the founding of the city itself. The foundation of Częstochowa can be, then, regarded as part of Casimir’s modernization effort in the Kingdom of Poland, since, in order to build a new route connecting Cracow with Greater Poland and Silesia, it was crucial to build a crossing over the river Warta in the vicinity of the Częstochowa village and the subsequent location of the city.